Indian cinema : filmic content, social interface and new technologies - Vikrant Kishore, Ed; Ambrish Saxena, Ed (Kanishka, 2019)
Indian society despite economic growth is still facing the issues of freedom and equality. Women, minorities and downtrodden sections of society are fighting for their due status in society. These issues surface in all kind of literature and art forms. Indian cinema also takes this narrative forward by creating some really good films.